Comunicación estratégica en el impulso de emprendimientos comunitarios con mujeres montubias del cantón Mocache, año 2021 - Maldonado Piloso, Hugo Fabricio (2021)
The present research work was carried out with the objective of diagnosing the incidence of strategic communication in promoting community enterprises with montubia women in the Mocache city, based on the needs and problems that affect these places. In order to improve the socioeconomic development of the inhabitants of the "San Mateo" recital located in the Mocache city. This research study seeks to create insertion opportunities for Montubia women in a community entrepreneurship business. Currently, all community ventures are established as incentives for communities so that they are able to create, manage and develop projects that generate economic sustainability for their families and community. The development of this project is focused on identifying the references on communication strategies in the application of community enterprises, analyzing the current level of entrepreneurship and skills of Montubia women in the rural sectors of the Mocache city. To determine the proposed objectives, statistical tests were carried out through the application of 50 surveys, out of a total of 100 women who live in the “San Mateo” enclosure, all this allowed to know and diagnose the importance of strategic communication in promoting entrepreneurship and demonstrate the interest of these women to receive training that allows them to develop their skills to the maximum in each activity that concerns the entrepreneurial business. To carry out the project, I have the support of the leader of the recite “San Mateo and the unavoidable initiative of the entire community.